2022
DOI: 10.1021/acs.jpcc.2c01259
|View full text |Cite
|
Sign up to set email alerts
|

ATR-SEIRAS Investigation of the Electro-oxidation Mechanism of Biomass-Derived C5 Furanics on Platinum Electrodes

Abstract: The electrochemical oxidation of furfural and down-pathway intermediate and product species (furoic acid, 2­(5H)-furanone, 5-hydroxy-2­(5H)-furanone, and maleic acid) is investigated on platinum electrodes via attenuated total reflectance surface-enhanced infrared absorption spectroscopy (ATR-SEIRAS) with modulation excitation spectroscopy (MES). Density functional theory (DFT) calculations are performed to further illuminate the elementary reaction mechanism and the surface orientations of key reaction interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 64 publications
2
28
0
Order By: Relevance
“…A research challenge ahead will be developing sophisticated transport models to accurately determine how these gradients develop over the electrode and understand how they impact overall activity and selectivity [83] . The design principles of this reactor can enable vibrational spectroscopy studies of electrochemical reactions in a wide range of electrolytes, mass transport conditions, and electrocatalysts, accelerating fundamental understanding of the CO 2 RR, and the electrocatalytic conversions of other small (O 2, CH 4 , CO, N 2 , H 2 O, NO x ) [2–7] and complex bio‐derived molecules [8,9] relevant for sustainable technologies and chemical‐dependent industries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A research challenge ahead will be developing sophisticated transport models to accurately determine how these gradients develop over the electrode and understand how they impact overall activity and selectivity [83] . The design principles of this reactor can enable vibrational spectroscopy studies of electrochemical reactions in a wide range of electrolytes, mass transport conditions, and electrocatalysts, accelerating fundamental understanding of the CO 2 RR, and the electrocatalytic conversions of other small (O 2, CH 4 , CO, N 2 , H 2 O, NO x ) [2–7] and complex bio‐derived molecules [8,9] relevant for sustainable technologies and chemical‐dependent industries.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we observed a 6-fold improvement in CO partial current densities at À 1 V vs RHE with a similarly rough Au catalyst over the benchmarked reactor, which we attributed to the enhanced mass transport (Note S3); however, electrolyte impingement on the electrode is expected to induce complex concentration gradients across the electrode during CO 2 R. [82] A research challenge ahead will be developing sophisticated transport models to accurately determine how these gradients develop over the electrode and understand how they impact overall activity and selectivity. [83] The design principles of this reactor can enable vibrational spectroscopy studies of electrochemical reactions in a wide range of electrolytes, mass transport conditions, and electrocatalysts, accelerating fundamental understanding of the CO 2 RR, and the electrocatalytic conversions of other small (O 2, CH 4 , CO, N 2 , H 2 O, NO x ) [2][3][4][5][6][7] and complex bio-derived molecules [8,9] relevant for sustainable technologies and chemical-dependent industries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such information in principle can be provided by vibrational spectroscopy studies at the metal−water interface. For example, Hasse et al 43 have employed surface-enhanced infrared spectroscopy to investigate furfural adsorption and electro-oxidation on Pt surfaces. They found that furfural adsorption was accompanied by some CO surface formation at low potentials, and that high (oxidizing) potentials led to surface oxidation of furfural to furoic acid and other surface-bound products.…”
Section: Enthalpy Of Adsorptionmentioning
confidence: 99%
“…The former issue can be resolved using IREs made from micromachined Si wafers. , The lower path length through silicon gives improved S/N from about 1400 cm –1 to the low-frequency limit of standard MCT detectors, and micromachined Si IREs have been used to great effect in electrochemical ATR-SEIRAS studies. Furthermore, rather than depositing gold directly on Si, SEIRAS-active films can be formed starting with an IRE coated with a thin film of conductive metal oxide (CMO) such as indium zinc oxide (IZO) or indium tin oxide (ITO) . Such layers are conductive and largely transparent at mid-IR wavelengths and adhere extremely well with Si surfaces.…”
mentioning
confidence: 99%